2017
DOI: 10.1371/journal.pmed.1002282
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a live oral human rotavirus vaccine after programmatic introduction in Bangladesh: A cluster-randomized trial

Abstract: BackgroundRotavirus vaccines are now globally recommended by the World Health Organization (WHO), but in early 2009 WHO’s Strategic Advisory Group of Experts on Immunization reviewed available data and concluded that there was no evidence for the efficacy or effectiveness of a two-dose schedule of the human rotavirus vaccine (HRV; Rotarix) given early at 6 and 10 wk of age. Additionally, the effectiveness of programmatic rotavirus vaccination, including possible indirect effects, has not been assessed in low-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 41 publications
0
82
0
Order By: Relevance
“…Consequently, introducing rotavirus vaccine in Bangladesh could prevent acute diarrheal episodes and reduce the contribution of diarrhea in childhood deaths. Although the rotavirus vaccine is not as effective in Bangladesh as compared with the high-income countries, it still prevented 41% of illnesses 27 which could substantially reduce the burden of diarrhea in Bangladesh. Ascertaining cause of death and attributing a single cause of death among children is a conceptual over-simplification as comorbidity often occurs and many circumstances contribute to child deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, introducing rotavirus vaccine in Bangladesh could prevent acute diarrheal episodes and reduce the contribution of diarrhea in childhood deaths. Although the rotavirus vaccine is not as effective in Bangladesh as compared with the high-income countries, it still prevented 41% of illnesses 27 which could substantially reduce the burden of diarrhea in Bangladesh. Ascertaining cause of death and attributing a single cause of death among children is a conceptual over-simplification as comorbidity often occurs and many circumstances contribute to child deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier results from high income countries of Asia in Hong Kong 7 and Japan 8 , where RVV are self-financed, revealed RVV effectiveness of 89% and 70%, respectively against diarrheal hospitalization. However, a cluster-randomized study conducted in Bangladesh, a low income country, revealed that the monovalent RVV effectiveness was 41.4% 9 .…”
Section: Introductionmentioning
confidence: 99%
“…29 The study on rotavirus vaccine 29 showed that only 68 (26%) of 258 of children who did not have increased rotavirus-specific IgA antibody-secreting cell levels at onset of vaccination developed significant IgA antibody-secreting cell responses to the rotavirus vaccine despite the same vaccine inducing protection in 45% of infants in similar populations in Bangladesh. 30 These results suggest that measuring circulating antibody-secreting cell or ALS responses is not optimal for assessment of mucosal immune responses to oral enteric vaccines in very young children. In this study, we show that secretory IgA anticolonisation factor antibody responses in faecal extracts were considerably more frequent in infants than were ALS IgA responses to the same antigens.…”
Section: Discussionmentioning
confidence: 97%